Pengaruh Self Control Terhadap Kecanduan Media Sosial pada Remaja Kota Padang - Pratiwi, Chici; Jannah, Adinda Miftahul; Dewita, Erna; Sari, Mezia Kemala; Maiseptian, Fadil (Universitas Mathla'ul Anwar Banten, 2024)
This research is motivated by the large number of adolescents or teenagers who spend their time playing on social media, so adolescents experience addiction, which causes individuals to forget their responsibilities. This research discusses how adolescent self-control and social media addiction are described, and their effects. This research aims to determine the description of self-control and social media addiction in adolescents, apart from that, to determine the influence of self-control on social media addiction among adolescents in Padang City. The research method used in this research is quantitative correlational. The subjects in this research were 52 teenagers in Padang City who had a high intensity in using social media. The data collection techniques used are research instruments, validity tests, and reliability tests. Next, the analysis prerequisite tests are the normality test and the linearity test. The data analysis technique used is a simple linear regression test. From the analysis results obtained, it is known that the average self-control possessed by Kampung Baru Lubuk Lintah teenagers is in the medium category, as well as social media addiction which is in the medium category. So it can be seen the influence of self-control on social media addiction. The higher an individual's level of self-control, the lower the level of social media addiction can be avoided. Conversely, if the level of self-control is low then social media addiction will increase.